Substance Use Among American Indian Youth: Epidemiology and Etiology, (United States), 2015-2020 - Swaim, Randall C. ([Verlag nicht ermittelbar], 2021)
This study is a continuation of an ongoing 40+ year surveillance effort assessing the levels and patterns of substance use among American Indian (AI) adolescents attending schools on or near reservations. The current set of data is from the most recent funding cycle, 2015-2020. During this funding cycle, annual samples across various geographic regions in which reservation-based AI residents reside were obtained and school-based surveys were completed. In addition to the annual epidemiology of substance use, data pertaining to risk and protective factors, including cultural-ethnic identity, perceived discrimination, family factors, and individual risk and protective factors were obtained. It should be noted that two major changes were made during this funding cycle: 1) The wording of substance use variables was altered to mirror wording from Monitoring the Future to allow for direct comparisons between the two studies. 2) All data during this funding cycle were obtained online using Qualtrics.